Analisis Kalimat Elipsis Yang Terdapat Pada Tweet Akun Twitter Berbahasa Jepang - Adani, Ghauthiah; Wikarya, Rahmi Oktayory (Universitas Negeri Padang, 2024)
Japanese is a language that often experiences ellipsis, there are many sentences in Japanese that end with particles, making the sentence incomplete and one of the characteristics of Japanese. An ellipsis is an omission of a sentence element which can be easily interpreted by the interlocutor himself. This, in addition to avoiding speakers who seem convoluted. The purpose of this study is to describe what types of elipsis sentences are often used in personal account tweets in Japanese. The research method used is descriptive qualitative research type. The technique of collecting data from this research is to see notes. The subject of this is a tweet on a personal Japanese Twitter account. The results of this study indicate as many as 30 types of ellipsis sentences which include 3 verbal ellipsis, 6 clause ellipsis, and 22 particle ellipsis. The ellipsis type of sentence that is often used by Twitter users when writing Japanese tweets from 30 September 2022 to 03 October 2022 with a 24-hour window is the particle ellipsis.